2020
DOI: 10.1111/scd.12454
|View full text |Cite
|
Sign up to set email alerts
|

Oral management of pemphigus vulgaris in the intensive care unit

Abstract: Pemphigus vulgaris (PV) is a rare and potentially lethal autoimmune disease that affects the skin and mucous membranes. Injuries caused by the disease cause pain, risk of infection, and other complications that result in a high mortality rate. Frequently, management of the PV requires intensive care and a multidisciplinary approach. Oral lesions of PV are usually the first clinical signs of the disease and the last lesions to heal, requiring treatment by a specialized dental team. The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In 11 studies (84.6%), the laser was applied singly and in 2 studies (15.4%), it was used concurrently with steroid therapy (Table 1 ). Five articles reported the effect of the laser directly on the gingival tissues [ 14 , 30 , 38 , 41 , 48 ]. Three studies [ 14 , 30 , 38 ] showed that all gingival cases were successfully treated with PBM, while two studies [ 41 , 48 ] reported unsatisfactory response to the laser for some patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 11 studies (84.6%), the laser was applied singly and in 2 studies (15.4%), it was used concurrently with steroid therapy (Table 1 ). Five articles reported the effect of the laser directly on the gingival tissues [ 14 , 30 , 38 , 41 , 48 ]. Three studies [ 14 , 30 , 38 ] showed that all gingival cases were successfully treated with PBM, while two studies [ 41 , 48 ] reported unsatisfactory response to the laser for some patients.…”
Section: Resultsmentioning
confidence: 99%
“…Another autoimmune disease with an important oral manifestation is PV, comprising a group of rare autoimmune bullous diseases that affect the skin and mucous membranes [ 13 ]. Oral lesions usually precede skin lesions or are the only manifestation of the disease, affecting areas such as the lips, gingiva, oral mucosa, and palate [ 14 ]. Oral manifestations of PV can be very painful, disrupting oral intake and, consequently, affecting patients’ quality of life on a negative manner [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diagnosis of the PV is based on identification of clinical manifestations and confirmation by incisional biopsy of the affected perilesional tissue of the skin or mucous membranes [ 13 ]. Clinically, oral lesions are the first manifestations of the disease in 50-90% of the patients with widespread blisters affecting the oral mucosa, most commonly in areas subjected to frictional trauma [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In oral lesions, topical corticosteroids can be applied along with systemic treatments; however, the concomitant use of biomodulation through low-level laser therapy has been recently shown to regulate pain and promote analgesia, in addition to the significant healing benefit. 21 azathioprine are effective options. 27 Recently, some alternative therapies such as medicinal herbs and ozone therapy have been proposed.…”
Section: Discussionmentioning
confidence: 99%